English for Political Science. Professional English for Political Science, International Relations, History and Related Subjects. A Textbook. - FĂTU-TUTOVEANU, Andrada; BERCUCI, Loredana; GRĂDINARU, Olga (2026)
This textbook was designed as very interactive – with communication activities, readings (excerpts of actual state-of-the-art research in the field), debates, projects and different exercises around important political phenomena from a contemporary approach. Among the topics around which the units are organised are the media and politics, national identity, political myths and symbols in political communication, wars and conflicts, hostile imagery and propaganda.The aim of the current textbook is to provide students and scholars in the field of Political Science, International Relations, History, Conflict Studies and related fields with the opportunity to develop their knowledge of professional English as well as enable them to communicate about topical issues in their area of expertise. The authors intended the textbook to have a particular focus on vocabulary but also include visual aids and multimedia references, in an interdisciplinary approach that is inherent to the fields. We hope this will prove a stimulating instrument for all users and enhance their communication skills in English as well as their interest in the field.